Lipid profile changes in second trimester of pregnancy - Husain, F; Latif, SA; Uddin, MM; Nessa, A (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jan;17(1):17-21. The abstract of this article is available on the PubMed website